INFILTRATION CHARACTERISTICS OF SOIL UNDER EUCALYPTUS PLANTATION FOREST IN HEADWATER OF VIETNAM - Xuan Dung, Bui; Thi My Linh, Nguyen; Thi Thuy, Tran; Nguyen Kha, Le; Thuy Linh , Pham; Thi Thu Trang, Pham (Journal of Forestry Science and Technology, 2017)
To determine soil infiltration characteristics of eucalyptus plantation forest, we used double rings infiltrometer in 15 different locations (5 times for one part) of up-hill, mid-hill and down-hill parts from August 2015 to March 2016. Dye pouring method was also used to determine spatial distribution of infiltration in two plots (Eucalyptus tree plot and reference plot- no eucalyptus trees). Some other factors that can impact on soil infiltration such as soil physical, understory vegetation were determined. Main findings of this study include: (1) Infiltration rate tended to be decreased over time, the rate was highest at the downhill and lowest at the middle hill; (2) Spatial infiltration distribution of dye in two plots was different, dye tended to be infiltrate deeper and bigger area into soil at reference plot; (3) Infiltration rate did not have close relationship with soil moisture and porosity but it strongly depended on understory vegetation. However, infiltration rate have close relationship with overall factors (vegetation cover, soil moisture and porosity). These findings suggest that water demand of Eucalyptus tree for growth has limited deeper infiltration capacity and make drier soil under Eucalyptus forest.